2022
DOI: 10.3389/fgene.2022.990623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel m5C/m6A-related gene signature for predicting prognosis and immunotherapy efficacy in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is the most prevalent subtype of non-small cell lung cancer (NSCLC) and is associated with high mortality rates. However, effective methods to guide clinical therapeutic strategies for LUAD are still lacking. The goals of this study were to analyze the relationship between an m5C/m6A-related signature and LUAD and construct a novel model for evaluating prognosis and predicting drug resistance and immunotherapy efficacy. We obtained data from LUAD patients from The Cancer Genome Atlas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…43 A growing number of studies are finding possible links between different RNA modification regulators. 17,18,[44][45][46][47] NSUN2 catalyzes m5C modification and METTL3/METTL14 m6A modification in the three "non-coding" regions of p21 mRNA, in addition, methylation of METTL3/METTL14 promotes methylation of NSUN2 and vice versa. 18 EIF3A may play the role of a chaperone protein as a reader of NOP2 (m5C binding protein), thus regulating NOP2-mediated m5C modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 A growing number of studies are finding possible links between different RNA modification regulators. 17,18,[44][45][46][47] NSUN2 catalyzes m5C modification and METTL3/METTL14 m6A modification in the three "non-coding" regions of p21 mRNA, in addition, methylation of METTL3/METTL14 promotes methylation of NSUN2 and vice versa. 18 EIF3A may play the role of a chaperone protein as a reader of NOP2 (m5C binding protein), thus regulating NOP2-mediated m5C modification.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies are finding possible links between different RNA modification regulators 17,18,44–47 . NSUN2 catalyzes m5C modification and METTL3/METTL14 m6A modification in the three “non‐coding” regions of p21 mRNA, in addition, methylation of METTL3/METTL14 promotes methylation of NSUN2 and vice versa 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al have constructed a risk model by using 5 m 5 C RNA regulators, including ALYREF, to classify patients with lung cancer into high-risk (poorer OS) and low-risk (better response to immune checkpoint blockade therapy) groups [26]. Similarly, Ma et al have constructed a prognostic risk model by using m 5 C/m 6 A-related gene signatures including ALYREF to evaluate prognosis and predict drug resistance and immunotherapy efficacy [17]. The functional roles of ALYREF in NSCLC have not been well studied thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ALYREF is involved in tumor cell proliferation, metabolism, and metastasis [14][15][16]. The roles of ALYREF in NSCLC remain unclear although a recent study suggests that it, together with other m 5 C/m 6 A-related genes, could predict prognosis and immunotherapy efficacy in lung cancer [17]. Therefore, we first investigated the expression pattern and biological function of ALYREF in NSCLC.…”
Section: Alyref Is Upregulated In Nsclc and Promotes Nsclc Progressionmentioning
confidence: 99%
“… 8 Further, researches reported that the novel m5C-related molecular subtypes of LUAD cohorts were constructed by unsupervised clustering analysis to assess the similarity and difference information in m5C methylation as well as m5C gene expression patterns of LUAD samples, providing a preliminary rationale for further screening of key genes in LUAD progression. 9 , 10 On the other hand, the immune related prognostic signature for predicting survival of LUAD cohorts has been explored, 11 Inspired by these studies, the relationship of m5C methylation and immune microenvironments alterations was revealed gradually. 12 Therefore, it is of great significance to search for novel therapeutic directions such as immune-related genes significantly associated with m5C methylation (m5C-IRGs) in LUAD for early diagnosis and prognosis assessment of LUAD patients.…”
Section: Introductionmentioning
confidence: 99%